PENYULUHAN PERAWATAN PAYUDARA SEBAGAI PERSIAPAN MASA LAKTASI PADA IBU HAMIL DI PUSKESMAS MUTIARA BARAT TAHUN 2022 - Zaitun, Zaitun; Salamah, Salamah; Nurmeliana, Nurmeliana (COVIT (Community Service of Tambusai), 2022)
Breast care is very important during pregnancy until breastfeeding. This is because the breast is the only producer of breast milk which is the staple food for newborns, so it must be done as early as possible. Breast care aims to maintain the cleanliness of the breast, increase or expedite the release of breast milk. The purpose of this community service is to prepare pregnant and postpartum women to be in good condition when breastfeeding their babies and to be able to demonstrate proper breast care independently at home. The community service method uses an educative approach on breast care for pregnant women at the Mutiara Barat Health Center in the form of lectures and questions and answers on breast care. The results of this community service are maintaining the cleanliness of the breasts, especially the cleanliness of the nipples, flexing and strengthening the nipples so that it is easier for the baby to suckle, stimulating the milk glands so that milk production is abundant and smooth, can detect breast abnormalities early and make efforts to overcome them and preparing the mother's mental (psychological) for breastfeeding. It is hoped that after an educational approach is taken, pregnant women will have more knowledge and be able to prepare for exclusive breastfeeding for their babies. Keywords: Counseling, Breast care